Creating Markets in Sri Lanka : Private Sector-Led Inclusive Growth from Islands of Excellence : Country Private Sector Diagnostic - International Finance Corporation (World Bank, Washington, DC, 2022)
Sri Lanka is a country of paradoxes. With the lowest poverty rates, best social indicators, and highest per capita income in South Asia, Sri Lanka’s economic performance since independence had generally been hailed as a success before the current debt crisis. However, past performance occurred amidst many distortions and an economy less open than its peers, largely reflecting the strong involvement of the state in the economy. Even if this interventionist model of economic policy and the presence of many state-owned enterprises (SOEs) served the country well through the years of conflict and their aftermath, it is no longer sustainable. Indeed, after the rapid growth of the peace dividend in the years post-2009, the economy has faltered and progress on social indicators has stagnated. Many of market distortions remain and have been exacerbated by COVID-19. Understanding how, despite these handicaps, Sri Lanka achieved positive economic and social outcomes in the past provides the building blocks of a realistic, forward-looking growth strategy, one of the objectives of this Country Private Sector Diagnostic (CPSD). The research for this report was conducted prior to the current crisis, but the recommendations remain relevant to implementing public policies that will support private sector-led inclusive and sustainable growth.